Biologic switching patterns among children with non-systemic juvenile idiopathic arthritis - Mia Lindegaard Pedersen; Amalie Neve-Græsbøll; Troels Herlin; Mia Glerup (BMC, 2023)
Abstract Background In juvenile idiopathic arthritis (JIA) clinical remission is unattainable in some patients despite modern biologic disease-modifying antirheumatic drugs (bDMARD) therapy and switching bDMARD is required. The best choice of second-line bDMARD remains unclear. This retrospective observational study aims to describe the pattern, timing, frequency, and reasons for bDMARD switching among children diagnosed with non-systemic JIA. Methods Patients were identified by combining unique personal identification numbers, the International Code of Diagnosis (ICD10) for JIA and biologic therapy. Clinical characteristics were collected retrospectively from the electronic medical records. Included were 200 children diagnosed with non-systemic JIA initiating their first biologic drug between January 1st, 2012, and March 1st, 2021. We compared characteristics of non-switchers vs switchers and early switchers (≤ 6 months) vs late switchers (> 6 months). Results The median age at diagnosis was 7.7 years. We found that 37% switched to a different bDMARD after a median age of 6.3 years after diagnosis. In total, and 17.5% of patients switched at least twice, while 6% switched three or more times. The most common reason for switching was inefficacy (57%) followed by injection/infusion reactions (15%) and uveitis (13%). 77% were late switchers, and switched primarily due to inefficacy. All patients started a tumor necrosis factor inhibitor (TNFi) as initial bDMARD (Etanercept (ETN): 49.5%, other TNFis: 50.5%). The patients who started ETN as first-line bDMARD were more likely to be switchers compared to those who started another TNFi. Conclusion During a median 6.3-year follow-up biologic switching was observed in more than one third, primarily due to inefficacy.